2013
DOI: 10.1002/pola.26607
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of porphyrin‐based D‐π‐A conjugated polymers for polymer solar cells

Abstract: Two novel porphyrin‐based D‐A conjugated copolymers, PFTTQP and PBDTTTQP, consisting of accepting quinoxalino[2,3‐b′]porphyrin unit and donating fluorene or benzo[1,2‐b:4,5‐b′]dithiophene unit, were synthesized, respectively via a Pd‐catalyzed Stille‐coupling method. The quinoxalino[2,3‐b′]porphyrin, an edge‐fused porphyrin monomer, was used as a building block of D‐A copolymers, rather than the simple porphyrin unit in conventional porphyrin‐based photovoltaic polymers reported in literature, to enhance the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Photoresponsive and electron conducting polymer materials are crucial components in applications such as solar cells, photovoltaics, organic electronics, and holographic data storage . Among the broad range of photoactive materials, the isomerization between norbornadiene (NBD) and quadricyclane (QC) is a promising system for the development of materials suitable for the storage and conversion of solar energy .…”
Section: Introductionmentioning
confidence: 99%
“…Photoresponsive and electron conducting polymer materials are crucial components in applications such as solar cells, photovoltaics, organic electronics, and holographic data storage . Among the broad range of photoactive materials, the isomerization between norbornadiene (NBD) and quadricyclane (QC) is a promising system for the development of materials suitable for the storage and conversion of solar energy .…”
Section: Introductionmentioning
confidence: 99%
“…Further work on the quinoxaline porphyrin D-A polymer system involved substituting the carbazole for a fluorene or benzodithiophene moiety, but these had limited effect on the photovoltaic performance with solar conversion efficiencies of 2.39% for the fluorene-containing polymer and 1.53% for the benzodithiophene-containing porphyrin polymer (Figs 39(j) and (k)). 113 Although these systems show good visible-light photovoltaic response, performance appears to be limited by low free charge carrier transport within the photoactive layer. Charge mobility and an overall increase in efficiency was recently obtained with a thiophen-2-ylbenzo-2,1,3-thiadiazole-based system which appended a diethynyl-containing porphyrin along the conjugated polymer backbone (Fig.…”
Section: Porphyrin Polymeric Solar Cellsmentioning
confidence: 99%
“…Hole mobilities may be limited by the close interaction between the porphyrin and the polymer chain forcing nonlinearity in the conjugated backbone. Further work on the quinoxaline porphyrin D–A polymer system involved substituting the carbazole for a fluorene or benzodithiophene moiety, but these had limited effect on the photovoltaic performance with solar conversion efficiencies of 2.39% for the fluorene‐containing polymer and 1.53% for the benzodithiophene‐containing porphyrin polymer (Figs (j) and (k)) . Although these systems show good visible‐light photovoltaic response, performance appears to be limited by low free charge carrier transport within the photoactive layer.…”
Section: Optoelectronic Applications Of Porphyrin Polymersmentioning
confidence: 99%
“…However, their use as pendent groups has actually proven their potential. For example, H. Wang et al have reported the synthesis of several conjugated polymers alternating electron‐rich units and poor “β‐fused” quinoxalino[2,3‐ b' ]porphyrins . Among these compounds, C‐TT‐QP and C‐TT‐QP‐Zn are composed of carbazole units and fused porphyrins which are separated by terthiophene bridges.…”
Section: Porphyrin‐containing Polymersmentioning
confidence: 99%